A STUDY OF THE RELATIONSHIP BETWEEN INSTRUCTORS’ PERCEPTIONS TOWARDS PROFESSIONAL DEVELOPMENT AND JOB SATISFACTION AT LITERATURE FACULTY OF YUNNAN NORMAL UNIVERSITY IN KUNMING, CHINA - Shen, Ziqian; Watana Vinitwatanakhun (Scholar: Human Sciences, 2022)
The main purpose of this study was to determine the relationship between instructors’ perceptions towards professional development and job satisfaction at the Literature Faculty of Yunnan Normal University in Kunming, China, during the academic year 2019 - 2020. The researcher surveyed 67 instructors from the Literature Faculty of Yunnan Normal University for this study. The main instrument used to collect data was a questionnaire to investigate instructors’ perceptions of professional development and job satisfaction. This study was based upon Guskey’s Theory of Professional Development and Herzberg’s Two-Factor Theory. The researcher used the Mean and Standard Deviation and Pearson Product Moment Correlation Coefficient to analyze the collected data. The Pearson correlation coefficient r was .500, with a significance value of .001. There was a relationship between instructors’ perceptions towards professional development and job satisfaction at the Literature Faculty of Yunnan Normal University in Kunming, China. Research findings indicated that instructors’ perceptions towards professional development had shown a “high” (4.50) level, and the level of instructors’ perceptions towards job satisfaction was also regarded as “high” (4.47).